Charkha: Focal Thing, Appropriate Technology, and the Wheel of Self-Reliance. - Kour, Rasleen (Techné: Research in Philosophy & Technology, 2024)
The Charkha, or the spinning wheel, a symbol of self-sufficiency and freedom, implicitly promoted the idea of togetherness, as it makes people sit and spin yarn together while they share joy and agony. This paper highlights the charkha as an epicenter, where it assimilates all the attributes and values of the focal thing (pre-technological life), a concept developed by Albert Borgmann in contrast to the device paradigm (modern technology). The paper has three objectives: first, to understand how the charkha may be developed as a model artifact in the context of Gandhi's philosophy; second, to highlight the conceptual proximity between Borgmann's and Gandhi's ideas of harmonious relation between humans and technology through skill and engagement; and lastly, reading Gandhi through Borgmann, the paper explores the charkha as a focal thing that provides people with a meaningful way of living where it tends to unify means and ends, labor and leisure.